The Effect Of Nutritional Therapy And Supplements On Immune Status And Energy Levels In People Living With Hiv/Aids Undergoing Antiretroviral Therapy - Siwi Wulandari; Utomo, Bram Mustiko (Journal for Quality in Women's Health, 2025)
HIV/AIDS remains a global health challenge, particularly in maintaining the quality of life for People Living with HIV/AIDS (PLWHA) undergoing antiretroviral therapy (ARV). Side effects of ARVs, such as fatigue, metabolic disorders, and loss of appetite, often disrupt the nutritional status, immunity, and energy levels of PLWHA. A quantitative experimental study with a pre-test and post-test design was conducted, involving 30 PLWHA who participated in an 8-week intervention of nutritional and supplement therapy.